The scandalous secret of abigail macgregor ebook - Quinn, Paula (MacGregors: Highland Heirs, 2015)
A LADY'S MISSION . . . Known for her beauty and boldness, Abigail MacGregor must preserve her clan's dangerous secret: that her mother is the true heir to the English Crown. If the wrong people find out, it will mean war for her beloved Scotland. To keep peace, she embarks for London, unprepared for the treachery that awaits-especially from her wickedly handsome escort. He is the enemy, but his slow, sensuous kisses entice her beyond reason . . . A WARRIOR'S TEMPTATION General Daniel Marlow, loyal knight and the kingdom's most desirable hero, would rather be on the battlefield than transporting a spoiled Highland lass. But Abby MacGregor is unlike any woman he's ever met, in a ballroom or in his bedroom. Captivated by her daring spirit and seduced by her lovely innocence, Daniel must choose between betraying his queen or giving up the woman who would steal his country-and his traitorous heart.